Steady states of $Λ$-type three-level systems excited by quantum light in lossy cavities - Rose, H.; Tikhonova, O. V.; Meier, T.; Sharapova, P. (arXiv:2109.00842)
The interaction between quantum light and matter is being intensively studied for systems that are enclosed in high-$Q$ cavities which strongly enhance the light-matter coupling. However, for many applications, cavities with lower $Q$-factors are preferred due to the increased spectral width of the cavity mode. Here, we investigate the interaction between quantum light and matter represented by a $Λ$-type three-level system in lossy cavities, assuming that cavity losses are the dominant loss mechanism. We demonstrate that cavity losses lead to non-trivial steady states of the electronic occupations that can be controlled by the loss rate and the initial statistics of the quantum fields. The mechanism of formation of such steady states can be understood on the basis of the equations of motion. Analytical expressions for steady states and their numerical simulations are presented and discussed.

Spectrally multimode integrated SU(1,1) interferometer - Ferreri, Alessandro; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina R. (Quantum)
Nonlinear SU(1,1) interferometers are fruitful and promising tools for spectral engineering and precise measurements with phase sensitivity below the classical bound. Such interferometers have been successfully realized in bulk and fiber-based configurations. However, rapidly developing integrated technologies provide higher efficiencies, smaller footprints, and pave the way to quantum-enhanced on-chip interferometry. In this work, we theoretically realised an integrated architecture of the multimode SU(1,1) interferometer which can be applied to various integrated platforms. The presented interferometer includes a polarization converter between two photon sources and utilizes a continuous-wave (CW) pump. Based on the potassium titanyl phosphate (KTP) platform, we show that this configuration results in almost perfect destructive interference at the output and supersensitivity regions below the classical limit. In addition, we discuss the fundamental difference between single-mode and highly multimode SU(1,1) interferometers in the properties of phase sensitivity and its limits. Finally, we explore how to improve the phase sensitivity by filtering the output radiation and using different seeding states in different modes with various detection strategies.

Managing spectral properties and Schmidt mode content of squeezed vacuum light using sum-frequency converter - Sukharnikov, Vladislav; Sharapova, Polina; Tikhonova, Olga (Optics & Laser Technology)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Komplexe Wörter richtig schreiben. Wortanalyse als Rechtschreibstrategie. - Lang, Susanne; Topalović, Elvira (In: Praxis Deutschunterricht)

Rechtschreibstrategien und Sprachstrukturen. - Noack, Christina; Topalović, Elvira (In: Praxis Deutschunterricht)

Reconfigurable quantum photonics with on-chip detectors - Gyger, S; Zichi, J; Schweickert, L; Elshaari, A.W; Steinhauer, S; Covre da Silva, S.F; Rastelli, A; Zwiller, V; Jöns, Klaus D.; Errando-Herranz, C

Engineering the Luminescence and Generation of Individual Defect Emitters in Atomically Thin MoS2 - Klein, J; Sigl, L; Gyger, S; Barthelmi, K; Florian, M; Rey, S; Taniguchi, T; Watanabe, K; Jahnke, F; Kastl, C; Zwiller, V; Jöns, Klaus D.; et al.

Quantum Teleportation with Imperfect Quantum Dots - Basso Basset, F; Salusti, F; Schweickert, L; Rota, M.B; Tedeschi, D; Covre da Silva, S.F; Roccia, E; Zwiller, V; Jöns, Klaus D.; Rastelli, A; Trotta, R

Quantum dots as potential sources of strongly entangled photons: Perspectives and challenges for applications in quantum networks - Schimpf, C; Reindl, M; Basset, F.B; Jöns, Klaus D.; Trotta, R; Rastelli, A

Gate-Switchable Arrays of Quantum Light Emitters in Contacted Monolayer MoS2 van der Waals Heterodevices - Hötger, A; Klein, J; Barthelmi, K; Sigl, L; Sigger, F; Männer, W; Gyger, S; Florian, M; Lorke, M; Jahnke, F; Taniguchi, T; Watanabe, K; et al.

Quantum dot technology for quantum repeaters: from entangled photon generation toward the integration with quantum memories - Neuwirth, J; Basso Basset, F; Rota, M. B; Roccia, E; Schimpf, C; Jöns, Klaus D.; Rastelli, A; Trotta, R

Strain-Controlled Quantum Dot Fine Structure for Entangled Photon Generation at 1550 nm - Lettner, T; Gyger, S; Zeuner, K.D; Schweickert, L; Steinhauer, S; Hedlund, C. Reuterskiöld; Stroj, S; Rastelli, A; Hammar, M; Trotta, R; Jöns, Klaus D; Zwiller, V

Integrated photon-pair sources with nonlinear optics - Wang, Y; Jöns, Klaus D.; Sun, Z

Telecom-wavelength InAs QDs with low fine structure splitting grown by droplet epitaxy on GaAs (111) A vicinal substrates - Tuktamyshev, A; Fedorov, A; Bietti, S; Vichi, S; Zeuner, K.D; Jöns, Klaus D.; Chrastina, D; Tsukamoto, S; Zwiller, V; Gurioli, M; Sanguinetti, S

Resonance fluorescence from waveguide–coupled, strain–localized two–dimensional quantum emitters - Errando-Herranz, C; Schöll, E; Picard, R; Laini, M; Gyger, S; Elshaari, A.W; Branny, A; Wennberg, U; Barbat, S; Renaud, T; Brotons-Gisbert, M; Bonato, C; et al.

On-Demand Generation of Entangled Photon Pairs in the Telecom C-Band with InAs Quantum Dots - Jöns, Klaus D.; Zeuner, K.D; Schweickert, L; Hedlund, C.R; Lobato, C.N; Lettner, T; Wang, K; Gyger, S; Schöll, E; Steinhauer, S; Hammar, M; Zwiller, V

Experimentelle bruchmechanische Untersuchung eines clinchgeeigneten Bleches aus HCT590X mithilfe einer neuen Probengeometrie - Weiß, Deborah; Schramm, Britta; Neuser, Moritz; Grydin, Olexandr; Kullmer, Gunter

Effizienzsteigerung von Haushaltskühlgeräten durch polymergebundene Phasenwechselmaterialien - Sonnenrein, Gerrit

Systemtheorie von Hardware-in-the-Loop-Simulationen mit Anwendung auf einem Fahrzeugachsprüfstand mit parallelkinematischem Lastsimulator - Olma, Simon

Systematik zur Evolution technischer Anforderungen - Lankeit, Christopher

Angehende (Religions-)Lehrkräfte begleiten aber wie?

Das Audioviduum. Eine Theoriegeschichte des Menschenmotivs in audiovisuellen Medien - Eckel, Julia

Islamischer Religionsunterricht. Beitrag zu einem friedlichen Zusammenleben - Elshahawy, Ahmed

The multiplicity of halal standards: a case study of application to slaughterhouses - Abdelrahem, Mohammed; Abdallah, Ali; Pasqualone, Antonella (Journal of Ethnic Foods)

Modellbasierte Synthese einer hybriden Kraft-/Positionsregelung für einen Fahrzeugachsprüfstand mit hydraulischem Hexapod - Kohlstedt, Andreas

W. M. Ormrod: Women and Parliament in Later Medieval England (The New Middle Ages) - Foerster, Anne (H-Soz-Kult)

Rissverhalten von unidirektionalen Flachsfaser-Epoxidharz-Verbunden infolge statischer Belastung - Keck, Stefan

„Power Poses“ – Fakten, frisierte Daten, Forschungslyrik? Ein Unterrichtsvorhaben zu Praktiken und Darstellungsformen psychologischer Forschung am Beispiel von nonverbaler Kommunikation - Schreiber, Christine; Scharlau, Ingrid; Patrzek, Justine (Psychologieunterricht)
Keywords: Unterrichtsfach Psychologie

Unterrichtsfach Psychologie an der Universität Paderborn - Patrzek, Justine; Buhl, Heike M.; Scharlau, Ingrid (Psychologieunterricht)
Keywords: Unterrichtsfach Psychologie

PIVOT: A Parsimonious End-to-End Learning Framework for Valuing Player Actions in Handball using Tracking Data - Müller, Oliver; Caron, Matthew; Döring, Michael; Heuwinkel, Tim; Baumeister, Jochen (8th Workshop on Machine Learning and Data Mining for Sports Analytics (ECML PKDD 2021))
Over the last years, several approaches for the data-driven estimation of expected possession value (EPV) in basketball and association football (soccer) have been proposed. In this paper, we develop and evaluate PIVOT: the first such framework for team handball. Accounting for the fast-paced, dynamic nature and relative data scarcity of hand- ball, we propose a parsimonious end-to-end deep learning architecture that relies solely on tracking data. This efficient approach is capable of predicting the probability that a team will score within the near future given the fine-grained spatio-temporal distribution of all players and the ball over the last seconds of the game. Our experiments indicate that PIVOT is able to produce accurate and calibrated probability estimates, even when trained on a relatively small dataset. We also showcase two interactive applications of PIVOT for valuing actual and counterfactual player decisions and actions in real-time.
Keywords: expected possession value; handball; tracking data; time series classification; deep learning

To the Moon! Analyzing the Community of “Degenerates” Engaged in the Surge of the GME Stock - Caron, Matthew; Gulenko, Maryna; Müller, Oliver (42nd International Conference on Information Systems (ICIS 2021))
In early 2021, the finance world was taken by storm by the dramatic price surge of the GameStop Corp. stock. This rise is being, at least in part, attributed to a group of Redditors belonging to the now-famous r/wallstreetbets (WSB) subreddit group. In this work, we set out to address if user activity on the WSB subreddit is associated with the trading volume of the GME stock. Leveraging a unique dataset containing more than 4.9 million WSB posts and comments, we assert that user activity is associated with the trading volume of the GameStop stock. We further show that posts have a significantly higher predictive power than comments and are especially helpful for predicting unusually high trading volume. Lastly, as recent events have shown, we believe that these findings have implications for retail and institutional investors, trading platforms, and policymakers, as these can have disruptive potential.
Keywords: Retail investors; GameStop; Social Networks; Reddit; WallStreetBets

Towards Quantum One-Time Memories from Stateless Hardware - Broadbent, Anne; Gharibian, Sevag; Zhou, Hong-Sheng (Quantum)
A central tenet of theoretical cryptography is the study of the minimal assumptions required to implement a given cryptographic primitive. One such primitive is the one-time memory (OTM), introduced by Goldwasser, Kalai, and Rothblum [CRYPTO 2008], which is a classical functionality modeled after a non-interactive 1-out-of-2 oblivious transfer, and which is complete for one-time classical and quantum programs. It is known that secure OTMs do not exist in the standard model in both the classical and quantum settings. Here, we propose a scheme for using quantum information, together with the assumption of stateless (i.e., reusable) hardware tokens, to build statistically secure OTMs. Via the semidefinite programming-based quantum games framework of Gutoski and Watrous [STOC 2007], we prove security for a malicious receiver making at most 0.114n adaptive queries to the token (for n the key size), in the quantum universal composability framework, but leave open the question of security against a polynomial amount of queries. Compared to alternative schemes derived from the literature on quantum money, our scheme is technologically simple since it is of the "prepare-and-measure" type. We also give two impossibility results showing certain assumptions in our scheme cannot be relaxed.
Keywords: Physics and Astronomy (miscellaneous); Atomic and Molecular Physics; and Optics

The Public Service Media and Public Service Internet Utopias Survey Report - Fuchs, Christian (The Public Service Media and Public Service Internet Manifesto)

Communicating COVID-19. Everyday Life, Digital Capitalism, and Conspiracy Theories in Pandemic Times. SocietyNow Series - Fuchs, Christian

History and Class Consciousness 2.0: Georg Lukács in the Age of Digital Capitalism and Big Data - Fuchs, Christian (Information, Communication and Society)

Marxist Humanism and Communication Theory. Media, Communication and Society Volume One - Fuchs, Christian

Engels@200: Friedrich Engels and Digital Capitalism. How Relevant Are Engels’s Works 200 Years After His Birth? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Engels@200: Friedrich Engels in the Age of Digital Capitalism. Introduction - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Cornel West and Marxist Humanism - Fuchs, Christian (Critical Sociology)

Das digitale Kapital. Zur Kritik der politischen Ökonomie des 21. Jahrhunderts - Fuchs, Christian

The Public Service Media and Public Service Internet Manifesto

Social Media: A Critical Introduction. Third English edition - Fuchs, Christian

The Future of Public Service Media and the Internet - Alessandro, D'Arma; Fuchs, Christian; Horowitz, Minna; Unterberger, Klaus (The Public Service Media and Public Service Internet Manifesto)

Introduction - Fuchs, Christian; Unterberger, Klaus (The Public Service Media and Public Service Internet Manifesto)

The Digital Commons and the Digital Public Sphere: How to Advance Digital Democracy Today - Fuchs, Christian (Westminster Papers in Communication and Culture)

How Did Donald Trump Incite a Coup Attempt? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Foundations of Communication/Media/Digital (In)Justice - Fuchs, Christian (Journal of Media Ethics)

Channel 4: Rather Than Privatising Public Service Media We Should Be Expanding It Online - Fuchs, Christian (The Conversation)

数字劳动与卡尔·马克思 - Fuchs, Christian

Enformasyon Çağında Marx Okumak. Kapital Cilt 1 Üzerine Bir Medya ve İletişim Çalışması - Fuchs, Christian

Soziale Medien und kritische Theorie. Second German edition - Fuchs, Christian

Membaca Kembali Marx Di Era Kapitalisme Digital - Fuchs, Christian

Dijital Kapitalizm Çağında Marx’ı Yeniden Okumak. BeneDijital Kapitalizm Çağında Marx’ı Yeniden Okumak - Fuchs, Christian

Imaginary multiquadratic number fields with class group of exponent $3$ and $5$ - Klüners, Jürgen; Komatsu, Toru (Mathematics of Computation)
In this paper we obtain a complete list of imaginary n-quadratic fields with class groups of exponent 3 and 5 under ERH for every positive integer n where an n-quadratic field is a number field of degree 2ⁿ represented as the composite of n quadratic fields.
Keywords: Applied Mathematics; Computational Mathematics; Algebra and Number Theory

Auslegung lastübertragender Klebverbindungen für den Landmaschinenbau - Laubrock, Miriam

Methode zur Prognose des Tragverhaltens von Halbhohlstanznietverbindungen - Giese, Patrick

Weiterentwicklung des einstufigen Widerstandselementschweißens - Janzen, Vitalij

Entwicklung eines selbstschließenden Vollstanznietverfahrens für das Fügen ultrahochfester Stahlwerkstoffe mit Aluminiumlegierungen - Sartisson, Vadim

Robotergeführtes Fließlochformschrauben hochfester Stahlwerkstoffe mit Aluminium-Strangpressprofilen - Zweck, Jonas

受众商品、数字劳动之争、 马克思主义政治经济学与批判理论 (The Audience Commodity, the Digital Labour Debate, Marxist Political Economy, and Critical Theory). - Fuchs, Christian (国外社会科学前沿 (International Journal of Social Science) 2021 (4))

Analyse von elektrischen Wärmeübertragungselementen unter Berücksichtigung des Kristallisationsfoulings in der Warmwasseraufbereitung - Janzen, Alexander

Dijital Nesneler, Digital Özneler - Büyük Veri Çağında Kapitalizm, Emek ve Siyaset Üzerine Disiplinlerarası Yaklaşımlar

弗洛姆与交往批判理论 - Fuchs, Christian (国外理论动态 (Foreign Theoretical Trends) 2021 (3))

Preface: Manfred Knoche’s Critique of the Political Economy of the Media and Communication [Preface to the article “Media Concentration” by Manfred Knoche] - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Thermal Neural Networks: Lumped-Parameter Thermal Modeling With State-Space Machine Learning - Kirchgässner, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (arXiv preprint arXiv:2103.16323)

Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Somatosensory perturbations influence cortical activity associated with single-limb balance performance - Sherman, David A.; Lehmann, Tim; Baumeister, Jochen; Grooms, Dustin R.; Norte, Grant E. (Experimental Brain Research)
Keywords: General Neuroscience

Assessing spreading and removal of virus laden aerosols in different settings using an aerosol method (Presentation) - Ludwig, Janis; Kykal, Carsten; Schmid, Hans-Joachim (Book of abstracts for the 2021 European Aerosol Conference)
Keywords: aerosol spreading; SARS-CoV-2; indoor air filtration

Synthese und asymmetrische Funktionalisierung von submikronen Janus-Polymer-Partikeln in der Gasphase (Poster) - Ludwig, Janis; Schmid, Hans-Joachim

Die Fussgänger*innen autonomer Kraftfahrzeuge. Eine informatische Dispositivanalyse - Matzner, Tobias (Autonome Autos – Die Zukunft des Verkehrs und die Dispositive der Mobilität)

Adaptation and Optimization of Planar Coils for a More Accurate and Far-Reaching Magnetic Field-Based Localization in the Near Field - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2021 Smart Systems Integration (SSI))

Low-Cost NB-IoT Microgrid Power Quality Monitoring System - Petrov, Dmitry; Kroschewski, Konstantin; Mwammenywa, Ibrahim; Kagarura, G. Mark; Hilleringmann, Ulrich (2021 IEEE Sensors)

Microcontroller Firmware Design for Industrial Wireless Sensors - Petrov, Dmitry; Kroschewski, Konstantin; Hilleringmann, Ulrich (2021 Smart Systems Integration (SSI))

Influence of electrode metallization on thin-film transistor performance - Reker, Julia; Meyers, Thorsten; Vidor, Fabio F.; Joubert, Trudi-Heleen; Hilleringmann, Ulrich (2021 IEEE AFRICON)

Detection of Defects on Irregular Structured Surfaces by Image Processing Methods for Feature Extraction - Sander, Tom; Lange, Sven; Hilleringmann, Ulrich; Geneis, Volker; Hedayat, Christian; Kuhn, Harald; Gockel, Franz-Barthold (2021 22nd IEEE International Conference on Industrial Technology (ICIT))

Development of Methods for Coil-Based Localization by Magnetic Fields of Miniaturized Sensor Platforms in Bioprocesses - Lange, Sven; Schroder, Dominik; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2021 22nd IEEE International Conference on Industrial Technology (ICIT))

ZnO nanoparticle films as active layer for thin film transistors - Hilleringmann, Ulrich (Nanostructured Zinc Oxide)

Complementary Inverter Circuits on Flexible Substrates - Reker, Julia; Meyers, Thorsten; Vidor, Fabio F.; Joubert, Trudi-Heleen; Hilleringmann, Ulrich (2021 Smart Systems Integration (SSI))

Integration Process for Self-aligned Sub-µm Thin-Film Transistors for Flexible Electronics - Reker, Julia; Meyers, Thorsten; Vidor, Fabio F.; Joubert, Trudi-Heleen; Hilleringmann, Ulrich (2021 IEEE International Conference on Flexible and Printable Sensors and Systems (FLEPS))

Entwicklung einer konstruktionsbasierten französischen Grammatik: ein Arbeitsbericht zum Adjektiv- und Nominalbandd

Grammatik des gesprochenen und geschriebenen Französisch: Das Nomen, - Siepmann, Dirk; Bürgel, Christoph

Lexiko-grammatische Konstruktionen als Kern der Spracharbeit im Spanischunterricht, in: Hispanorama

Hörverstehenskompetenz: Spanischstudierende auf dem Prüfstand der Abituraufgaben

Subjektwissen als Bildungsperspektive junger Erwachsener. Self-Tracking-Apps als digitale Optimierungstechnologien im Spannungsgefüge von Kontrolle und Selbstermächtigung - Burgfeld-Meise, Bianca; Dehmel, Lukas (Zeitschrift MedienPädagogik 42)

Dämpfungseigenschaften geklebter Verbindungen - Potenzialanalyse und Klebstoffcharakterisierung - Damm, Jannis; Albiez, Matthias; Göddecke, Johannes; Meschut, Gerson; Ummenhofer, Thomas (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Berufsausbildung in der Corona-Pandemie. Befunde studentischer Forschungsprojekte - Heisler, Dietmar (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Der Beitrag referiert Ergebnisse studentischer Forschungsprojekte, die sich mit den Folgen der Corona-Pandemie für die berufliche Bildung, für Berufswahl, Berufsvorbereitung und Ausbildung befasst haben. Die Ergebnisse zeigen nicht nur, wie unterschiedlich Berufe und Branchen von der Krise betroffen waren und damit umgegangen sind, sondern geben auch Hinweise auf nötige Weiterentwicklungen zur Verbesserung der Resilienz von Branchen, Berufen, Betrieben und ihrer Ausbildung.
Keywords: Pandemie; Distanzlernen; Berufswahl; Ausbildung

Das Analyseraster zu Merkmalen eines nachhaltigen Lernortes für betriebliche Ausbilderinnen und Ausbilder. - Heisler, Dietmar; Reißland, Jens; Müller, Claudia; Rühr, Laura; Gröger, Simon (Berufsbildung für nachhaltige Entwicklung. Die Modellversuche 2015-2019 auf dem Weg vom Projekt zur Struktur)

Berufsausbildung zwischen Attraktivitätsverlust und sozialer Ungleichheit Reformen für mehr Durchlässigkeit zwischen beruflicher und akademischer Bildung - Heisler, Dietmar (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Im Fokus steht das Problem der Durchlässigkeit von akademischer und beruflicher Bildung im Kontext aktueller Reformen. Die Erhöhung sozialer Mobilität als Reformziel gerät darin zugunsten der Attraktivitätssteigerung von Bildungsgängen aus dem Blick. Die geringe Durchlässigkeit von Bildungsgängen wird primär als Marketingproblem thematisiert.
Keywords: allgemeine Bildung; berufliche BIldung; Durchlässigkeit im Bildungssystem

On Existence of Ground States in the Spin Boson Model - Hasler, David; Hinrichs, Benjamin; Siebert, Oliver (Communications in Mathematical Physics)
We show the existence of ground states in the massless spin boson model without any infrared regularization. Our proof is non-perturbative and relies on a compactness argument. It works for arbitrary values of the coupling constant under the hypothesis that the second derivative of the ground state energy as a function of a constant external magnetic field is bounded.

Andrea Strübind / Klaas-Dieter Voß (Hgg.), Märtyrerbücher und ihre Bedeutung für konfessionelle Identität und Spiritualität in der Frühen Neuzeit. Interkonfessionelle und interdisziplinäre Beiträge zur Erforschung einer Buchgattung (SMHR 109), Tübingen 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Stefan Alkier (Hg.), Sola Scriptura 1517-2017. Rekonstruktionen – Kritiken – Transformationen – Performanzen (CHTh 7), Tübingen 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Hardware Trojans in Reconfigurable Computing - Ahmed, Qazi Arbab (2021 IFIP/IEEE 29th International Conference on Very Large Scale Integration (VLSI-SoC))

Einzelschulentwicklung gerecht und digital – Einblicke in die empirische Lage und Konsequenzen für die Praxis. - Schulze, Johanna (GGG-Magazin: DIE SCHULE für alle)

Medienkonzepte zur chancengerechten Schulentwicklung. Fallstudien an Schulen mit besonders herausfordernden Schüler*innenkompositionen. - Schulze, Johanna

Quantum optical coherence: From linear to nonlinear interferometers - Luo, Kai Hong; Santandrea, Matteo; Stefszky, Michael; Sperling, Jan; Massaro, Marcello; Ferreri, Alessandro; Sharapova, Polina; Herrmann, Harald; Silberhorn, Christine (Physical Review A)

Quantifying Quantum Coherence in Polariton Condensates - Lüders, Carolin; Pukrop, Matthias; Rozas, Elena; Schneider, Christian; Höfling, Sven; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (PRX Quantum)

Probing the topological Anderson transition with quantum walks - Bagrets, Dmitry; Kim, Kun Woo; Barkhofen, Sonja; De, Syamsundar; Sperling, Jan; Silberhorn, Christine; Altland, Alexander; Micklitz, Tobias (Physical Review Research)

Split-ring polariton condensates as macroscopic two-level quantum systems - Xue, Yan; Chestnov, Igor; Sedov, Evgeny; Kiktenko, Evgeniy; Fedorov, Aleksey K.; Schumacher, Stefan; Ma, Xuekai; Kavokin, Alexey (Physical Review Research)

Spin Polarization, Electron–Phonon Coupling, and Zero-Phonon Line of the NV Center in 3C-SiC - Jurgen von Bardeleben, Hans; Cantin, Jean-Louis; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Adsorption and Reaction of PbPc on Hydrogenated Epitaxial Graphene - Slawig, Diana; Gruschwitz, Markus; Gerstmann, Uwe; Rauls, Eva; Tegenkamp, Christoph (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials